Educator Equity Policy in The Era of Decentralization: A Triple Helix Approach Model - Septi Wulandari; Suprapti Suprapti; Esa Septian (PAEDAGOGIA, 2024)
Tripe Helix's Approach to Equitable Educator Quality Policy in the Era of Decentralization. One of the findings in the obstacles to the implementation of educational decentralization is the equal distribution of teaching staff equality. The efforts made by the central government to improve the standard of national education are carried out against the backdrop that it is on its way to achieving the goal of creating superior human resources. It is difficult to find human resources who are both academically capable and emotionally robust. In the decentralized age, this article seeks to offer a "triple helix" strategy for educational equity policies. For municipal leaders to succeed in decentralization, innovation and creativity are crucial. To achieve outcomes aimed at a national or even international level, leaders must be adept at managing local resources. In the spirit of NPM, where there is cooperation between the public and private sectors, the idea of decentralization is implemented. The Triple Helix theory is consistent with the ideas of decentralization and NPM. It was first popularized by Etzkowitz and Leydesdorff as a way to develop innovative policies. A literature analysis was the research methodology used. The information that the author used to create this article came from a study of several pertinent texts and research studies. This article's findings use the Triple Helix approach to achieve a balanced distribution of educators with the necessary credentials.